Pendidikan mengenai kesetaraan gender dan anti kekerasan dalam rumah tangga - Erna Dyah Kusumawati; Sasmini Sasmini; Adriana Grahani Firdausy (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
The number of victims of domestic violence in Indonesia is still considerably high. The aims of this community service are threefold. The first aim is to share knowledge with the community. Second is to increase the community’s legal awareness of the issue, and the third aim is to perform one task of the Tri Dharma Perguruan Tinggi. Such sharing knowledge is deemed to be beneficial both for the community and the university. This community service employed both lecturing and interactive discussion methods. Lecturing was used to deliver the materials, and discussion was used to further explore topics relating to the issues. These methods enable society’s acceptance and understanding. Prior to this activity, most participants did not comprehend the meaning of gender equality and its significant influence on family life. The participants informed that some forms of domestic violence occur in the neighbourhood. Previously, they were of the opinion that such incidents were families’ private matters. They neither have rights nor obligations to interfere. As community members, they have an obligation to prevent such incidents from happening and could also assist in protecting the victims by informing the police or local institutions established for prevention and handling domestic violence